Power harvesting through flexible rectenna at dual resonant frequency for low power devices - K. Singh, V; Saxena, Anurag; Bhushan Khare, Bharat; Shakya, Vicky; Soo Chae, Gyoo; Sharma, Ashis; Kumar Bhoi, Akash (International Journal of Engineering and Technology, 2018)
In Wireless power transmission, the transmission of electrical energy can be done without using any conductor or lead. After the simulation of wearable antenna, two resonant frequencies are obtained, i.e. 9.94 GHz and 7.35 GHz. For the designing of antenna, instead of using glass epoxy material, textile material is used having dielectric constant 1.7. The places where it is difficult to transfer the electrical energy, textile antenna is useful in those places. Ambient radio frequency can be converted in DC signal through the rectifier. All the graphs related to rectenna, such as return loss, output voltage and current at load are presented in this paper. Textile antenna for energy harvesting is de-signed in CST software and further rectenna circuit can be designed in Pspice Software.Â